Carbon-coated oxygen vacancies-rich Co3O4 nanoarrays grow on nickel foam as efficient bifunctional electrocatalysts for rechargeable zinc-air batteries. (1st June 2021) - Chen, Dongfang; Pan, Lyuming; Pei, Pucheng; Huang, Shangwei; Ren, Peng; Song, Xin
Abstract: The bifunctional electrocatalyst has an important influence on the power output and cycle life of rechargeable zinc-air batteries. Cobalt oxides, especially Co3 O4, have attracted much attention due to their high catalytic activity for oxygen evolution reaction (OER). It is difficult to improve the catalytic activity of oxygen reduction reaction (ORR) for rechargeable zinc-air batteries. In this paper, Co3 O4 containing rich oxygen vacancies is prepared by in-situ growth on the nickel foam, and the carbon coating treatment on the surface increases the conductivity and stability of Co3 O4, which prolongs its cycle life. The results show that moderate oxygen vacancies can achieve the best catalytic performance. The peak power density of zinc-air battery assembled by this air electrode can reach 54.5 mW cm −2, which is 51.4% higher than that of the untreated Co3 O4 catalyst. The cycle life of the battery can reach 716 cycles (358 h), prolonging about 250 h compared with Co3 O4 without carbon coating treatment. It is proved that the improved Co3 O4 can increase the power output and cycle life of the rechargeable zinc-air battery, which helps to expand the application range of cheap Co3 O4 catalyst, and provides an effective and economic solution to obtain excellent electrocatalysts for metal-air batteries. Graphical abstract: Image 1 Highlights: Carbon-coated oxygen vacancies-rich Co3 O4 nanoarrays were synthesized. Moderate oxygen vacancies significantly increased ORR/OER activity. Peak power density of battery is higher than that of untreated Co3 O4 . Coated carbon protected vacancies and prolonged cycle life to 358 h.